Design and prediction of dye dispersibility stabilized by polymeric dispersants using a Dye–Monomer interaction force measurement. (January 2020) - Kim, Gi Young; Perumal, Suguna; Kim, Soon Cheon; Lee, Sang-Ho; Noh, Seung Man; Park, Young Il; Cheong, In Woo; Kim, Jin Chul
Abstract: In this study, we propose a dye–monomer interaction force measurement technique based on atomic force microscopy (AFM) to predict the performance of polymeric dispersants. Cantilevers modified with functional monomers such as styrene, N -butyl acrylate (BA), and 2-( N -phthalimido)ethyl methacrylate (PEMA) were used to characterize the interaction force between these functional monomers and a target dye (Disperse Blue 359). The interaction forces of each monomer—styrene, BA, and PEMA—with Disperse Blue 359 were measured as 10.75 nN, 7.06 nN, and 21.31 nN, respectively, and their trend was consistent with dipole-moment values obtained from density function theory (DFT) calculations (μ(styrene) = 0.0001, μ(PEMA) = 2.3158, μ(Disperse Blue 359) = 3.0368). We synthesized a series of model polymers containing specific functional monomers (CoPS10, CoBA, CoPPEMAs) with similar molecular weights, molecular-weight distributions, and acid contents and compared their actual performance with that predicted from interaction force measurement data. The results were well correlated with the interaction force measurement data. The effect of the PEMA content on dye dispersion stability was also investigated; the results indicated that both the PEMA content and the type of dye-interacting group greatly influenced the characteristics of the dispersion. Highlights: Performance prediction of polymeric dispersant using atomic force microscopy (AFM). Measurement of interaction force of functional monomers with Disperse blue 359. Design of 2-(N-phthalimido)ethyl methacrylate as a new hydrophobic functional monomer. Preparation and characterization of polymeric dispersants. Comparison of actual performance of polymeric dispersants with predicative data.